Pengembangan Media Pembelajaran Video Berbasis Aplikasi CapCut Pada Materi Dinamika Litosfer Di SMA Negeri 1 Biluhu - Bano, Multiyawati A; Maryati, Sri; Yusuf, Daud (Universitas Negeri Gorontalo, 2025)
The aim of this research is to produce video learning media based on the CapCut application on lithospheric dynamics material at SMA Negeri 1 Biluhu. The method used in this research is ADDIE, which consists of analysis, design, development, implementation and evaluation stages. The data analysis technique used is descriptive qualitative. Based on the research results obtained, the development of video learning media based on the CapCut application received a very decent percentage score from geography experts and teachers. The percentage value of media experts is 96% (very feasible), the assessment by media experts is 85% (very feasible), while the assessment by learning is 96.66%. The student assessment obtained a score of 87.27 (very decent)